2020
DOI: 10.3389/fphys.2020.00149
|View full text |Cite
|
Sign up to set email alerts
|

The 24-Form Tai Chi Improves Anxiety and Depression and Upregulates miR-17-92 in Coronary Heart Disease Patients After Percutaneous Coronary Intervention

Abstract: Background: Anxiety and depression are common symptoms in patients with coronary heart disease (CHD) after percutaneous coronary intervention (PCI). The 24-form Tai Chi may exert a protective function for CHD patients after PCI by improving anxiety and depression.Methods: Patients who received PCI after 1-4 days were randomly assigned to the 24-form Tai Chi group (TG) and the control group (CG). The differences in anxiety and depression, using the Medical Outcomes Study 36−item Short−Form Health Survey (SF-36)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
41
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 64 publications
0
41
0
5
Order By: Relevance
“…In our study we found that weekly exercise offers protection against depression. Regular physical exercise is able to improve symptoms of anxiety and depression ( 19 ) and amplify positive emotions such as happiness and well-being ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our study we found that weekly exercise offers protection against depression. Regular physical exercise is able to improve symptoms of anxiety and depression ( 19 ) and amplify positive emotions such as happiness and well-being ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nesse contexto, a prática exercícios físicos se configura numa alternativa simples e barata para auxiliar no controle dos efeitos nocivos a saúde mental ocasionados pelo Distanciamento Social (Jiménez-Pavón, Carbonell-Baeza&Lavie, 2020). Afinal, a prática regular de exercícios físicos é capaz de melhorar sintomas de ansiedade e depressão (Liu, Yu, Lv& Wang, 2020) e amplificar emoções positivas como a felicidades e proporcionar bem-estar (Maher, Doerksen, Elavsky, Hyde, Pincus,Ram&Conroy, 2013). aeróbico quanto resistido deve ser moderada como intuito de maximizar os efeitos positivos no sistema imunológico (Joy, 2020).…”
Section: Exercícios Auxiliam a Saúde Mental Durante O Distanciamento unclassified
“…[ 5 ] What's more, mild to moderate intensity physical exercise is reported to have protective effects on survival for patients postPCI surgery. [ 6 ]…”
Section: Introductionmentioning
confidence: 99%